Effects of Atherectomy on Immediate Luminal Gain and Short-Term Patency in Patients With In-Stent Restenosis With or Without Stent Thrombosis - Michal S. Proczka; Crista E. Horton; Michal Macech; John J. Ricotta; Joseph J. Ricotta (Journal of Endovascular Therapy, 2026)
Purpose: Atherectomy may provide benefit by debulking lesions before angioplasty in patients with in-stent restenosis or stent thrombosis. This study evaluated immediate luminal gain, measured by intravascular ultrasound, achieved with excimer laser, solid-state laser, and rotational excisional atherectomy when treating femoropopliteal in-stent restenosis or stent thrombosis before angioplasty. Six-month patency was assessed by duplex ultrasound. Materials and Methods: We retrospectively analyzed 120 consecutive femoropopliteal interventions for >70% in-stent restenosis or chronic (>14 days) stent thrombosis (Rutherford class 3-5) performed in an office-based laboratory. Patients underwent atherectomy with excimer laser, solid-state laser, or rotational excisional atherectomy, followed by balloon angioplasty without drug-based devices or embolic protection. Intravascular ultrasound measured percent area stenosis before and after atherectomy to calculate luminal gain. Patency and >70% restenosis were assessed by duplex ultrasound at 1 and 6 months or earlier if symptom recurrence prompted target lesion revascularization. Statistical analysis used t tests, Mann-Whitney tests, analysis of variance, and chi-square tests, with significance set at P < .05. Results: Mean age was 74.5 years (95% CI, 72.9-76.2). Twenty-one patients (17.5%) were treated with excimer laser, 15 (12.5%) with solid-state laser, and 84 (70%) with rotational excisional atherectomy. Sixty-seven patients (55.8%) presented with in-stent restenosis and 53 (44.2%) with stent thrombosis. Stent length, number of stents, stent diameters, and Tosaka classes were similar across groups. Mean luminal gain did not differ between excimer laser (28.9%; 95% CI, 24.5-30.1) and solid-state laser (28.8%; 95% CI, 25.6-29.9). Rotational excisional atherectomy achieved significantly greater luminal gain (39.1%; 95% CI, 36.4-41.9) ( P < .001) and outperformed laser atherectomy for both in-stent restenosis ( P = .014) and stent thrombosis ( P < .001) subgroups. Six-month stenosis-free patency was highest with rotational excisional atherectomy (94%), compared with excimer laser (71.4%) and solid-state laser (73.3%) ( P < .004). Conclusions: Rotational excisional atherectomy was associated with greater immediate luminal gain and higher 6-month patency compared with excimer and solid-state laser atherectomy in the treatment of femoropopliteal in-stent restenosis and stent thrombosis. These findings suggest that rotational excisional atherectomy may have advantages over laser atherectomy for managing stent-related stenosis or thrombosis. Clinical Impact Rotational excisional atherectomy provides greater luminal gain and higher observed short-term patency compared with laser atherectomy in femoropopliteal in-stent restenosis and stent thrombosis. These findings suggest that rotational atherectomy may offer meaningful advantages in managing stent-related stenosis and thrombosis in the femoropopliteal segment.